2007
DOI: 10.1164/rccm.200704-587oc
|View full text |Cite
|
Sign up to set email alerts
|

Catamenial and Noncatamenial, Endometriosis-related or Nonendometriosis-related Pneumothorax Referred for Surgery

Abstract: Our experience shows that (1) CP and/or endometriosis-related pneumothoraces account for an important percentage of spontaneous pneumothoraces referred for surgery, (2) diaphragmatic abnormalities seem to play a fundamental role in their pathogenesis, and (3) management is difficult because of the high recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
173
0
32

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(208 citation statements)
references
References 18 publications
3
173
0
32
Order By: Relevance
“…Some procedures, such as thoracic tube aspiration, thoracotomy and bronchoscopy, can be used to identify endometrial implants. 10 Symptoms tend to be cyclic and to be worsened during menstruation. Clinical manifestations varies according to the affected areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some procedures, such as thoracic tube aspiration, thoracotomy and bronchoscopy, can be used to identify endometrial implants. 10 Symptoms tend to be cyclic and to be worsened during menstruation. Clinical manifestations varies according to the affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…14 The most common complementary test is the chest radiography which might reveal frequent changes such as pneumothorax, hemothorax with or without mediastinal deviation and parenchymatous nodules. 10 CT must be performed in symptomatic patients with normal chest radiography. Ca 125 level can also be elevated in those patients but this measure has low sensitivy and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with other recent studies, reported that 24.6%-29.0% of female SP patients were CP patients. [4][5][6] This increase was due to the fact that physicians were paying more attention to this disease. The median age of the CP patients was 39 years, which was consistent with other studies (31.9-35.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the CP patients was 39 years, which was consistent with other studies (31.9-35.0 years). [4][5][6] Many patients appear to develop CP in their thirties, which is older than the usual age when patients develop pelvic endometriosis (in their twenties). Twenty-seven of 28 cases with CP were rightsided.…”
Section: Discussionmentioning
confidence: 99%